Different selective dry cow therapy concepts compared to blanket antibiotic dry cow treatment - Seeth, Martin tho; Wente, Nicole; Paduch, Jan-Hendrik; Klocke, Doris; Vries, Elisabeth Mansion-de; Hoedemaker, Martina; Krömker, Volker (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2017)
Objective: The aim of the study was to investigate the use of somatic cell count (SCC) and aerobic bacterial counts as possible tools to choose animals for selective dry cow treatment (DCT) on cow level. Blanket antibiotic DCT is an approved and common method in Germany aimed at increasing the cure rate of existing intramammary infections (IMI) at the time of drying off and decreasing the risk of new infections during the dry period. However, not all animals benefit equally from an antibiotic DCT. Moreover, dairies, consumers and politicians demand a reduction in the use of antibiotics in farm animals. Several criteria for identifying animals which would benefit from antibiotic DCT have been described in the literature. Material and methods: Animals chosen for this investigation were divided into three study groups: Aerobic Count Petrifilm® group A (153 cows), SCC group S (160 cows) and control group C (169 cows). All quarters were treated with an internal teat sealant (ITS) no matter which group the cows belonged to. Results: Group C, in which all cows received an antibiotic DCT, achieved the best results referred to udder health, particularly regarding bacteriological dry period cure. However, the results of the two study groups A and S, in which the animals were dried off selectively, were only marginally worse. A significant difference regarding bacterial dry period cure was revealed between group S and group C (p = 0.039), whereas no significant difference concerning new IMI risk could be detected between the three study groups. Compared to a blanket antibiotic DCT of all cows in the corresponding study group, a reduction of the usage of antibiotics of 23.5 % (A) and 55 % (S) was noticed, respectively. Furthermore, it could be shown that the lactation number as well as the microorganisms present at the time of drying off influence udder health. Conclusion: Selective DCT is an alternative method to the widespread blanket antibiotic DCT. However, it has to be mentioned that selective DCT involves the described marginal decline in udder health and the additional amount of time, which might arise from the procedure of choosing the right animals and performing the applied rapid test methods.
Keywords: Dairy cow; dry period; selective dry cow treatment; udder health; intramammary infection